Comparing the environmental impact of using various energy sources in family house heating systems - Henryk Manteufel; Marcin Bukowski (Economic and Environmental Studies (E&ES), 2013)
Environmental impacts of using various sources of energy in heating a family house with 180 m2 of floor surface were compared by means of the SimaPro computer programme and attached to its databases, describing the environmental impacts of using typical materials and technologies. The set of compared heat energy sources comprised a ground loop, a heat pump, a liquid gas combustion furnace, an earth gas combustion furnace, a coal combustion furnace, a straw combustion furnace, a wood combustion furnace and an electric stove. After normalisation (which meant recalculating the impacts into their shares in the average impact of the kind, experienced by an average European in a year), weighting (which meant attaching arbitrary weights to three aggregate impact categories according to a methodology Eco-indicator 99 E/E) and aggregating the results into so called eco-points the wood combustion furnace turned out to have the greatest impact. It was followed by a coal burning furnace, an electric stove and an oil burning furnace. The heat pump had the smallest impact. A big impact of the wood and other biomass burning furnaces was due to a high emission of CO presumed in the used database, which can be disputed.
Keywords: 330; family house heating; environmental impact; SimaPro application; Eco-indicator 99